MOTIVASI SOSIAL DALAM RITUS TAREKAT QODIRIYAH NAQSABANDIYAH (Studi Ritus Selasan di Masjid Al Bukhori Mojoroto Gelanglor Sukorejo Ponorogo) - Djohan, M. Widda (IAIN Ponorogo, 2016)
Abstract: Spiritual intelligence (SQ) is the highest intelligence of human beings. There is correlation between spiritual intelligence and Allah. On the other word, someone who has spiritual intelligence should have highest relationship with Allah S. W. T. Then, its relationship affected interaction among others because of Allah aided. Tarekat Qodiriah wa Naqsyabandia is one of the spiritual activities and it held at Masjid Al Bukhari Mojoroto Gelanglor Sukorejo Ponorogo. This activity is expected to increase spiritual intelligence of the pilgrims.To uncover those phenomenon, this study formulate the problem as follows 1) How is the implementation of Tarekat Qodiriah wa Naqsyabandiah at Masjid Al Bukhori Mojoroto Gelanglor Sukorejo Ponorogo ? 2) How are the pilgrims whose join Tarekat Qodiriah wa Naqsyabandiah at Masjid Al Bukhori Mojoroto Gelanglor Sukorejo Ponorogo? 3) What are the roles of Tarekat Qodiriah wa Naqsyabandiah to increase spiritual intelligence of the pilgrims in Pondok Pesantren Darul Ulum Poncol, Magetan?. This study conducted Descriptive Qualitative approach. Interview, observation, documentation were used to collect the data.Those found that (a) the implementation of Tarekat Qodiriah wa Naqsyabandiah at Masjid Al Bukhari Mojoroto Gelanglor Sukorejo Ponorogo is held thirty-five a days on Minggu (Sunday) Wage. Furthermore, their activities are dzikir, istighosah, khususiah, reviewing Kitab, and manaqib. (b) There are diverse social stratification of the followers such high, low, and medium stratum. They are almost 30 years old. (C) The activities of Tarekat Qadiriah wa Naqsabandiah at Masjid Al Bukhari Mojoroto Gelanglor Sukorejo Ponorogo have important roles in increasing Spiritual Intelligence, because the main sets of this activity provides one’s moral and social intelligences, able to manage themselves and have good relationship among others. Those are based on human faith and devotion.Keywords: Spiritual Intelligence (SQ), Tarekat Qodiriah wa Naqsyabandiah